Repeatability of auxiliary sire indices with different progeny group size - Sahana, G; Gurunani, M (The Indian Journal of Animal Sciences, 2012)
The repeatability of auxiliary sire indices was examined using first lactation data of Holstein-Friesian crossbred cows. Age at first calving (AFC), first service period (FSP), first lactation length (FLL), first dry period (PDP) and first calving interval (FCI) were used as auxiliary traits in the present study. There was 5.26% increase in accuracy of sire evaluation when FLL was used as auxiliary trait, for other auxiliary traits the gain was very less. Similarly, number of daughters' records required for a pre-assigned level of accuracy was also less in case of FLL as auxiliary trait. The repeatability of breeding value estimates was obtained by determining the correlation of the breeding value of sires' estimate based on 5, 8 and 12 daughters with that of 'true' breeding value (based on 15 or more daughters record). The repeatability of auxiliary sire evaluation was higher when progeny group size per sire was small ranging from 5 to 8. With the increase of daughter number there was no advantage of incorporation of auxiliary traits over sire evaluation based on milk yield record of daughters.